Calibration and measurement of X-ray personal dose equivalent with a Hp(10) ionization chamber - Xu Yang (VINCA Institute of Nuclear Sciences, 2021)
The value of the personal dose equivalent at a 10 mm depth is to characterize the energy deposition of strong penetrating radiation in the human body and is derived by measurement of air kerma and application of conversion coefficients from the ISO report. However, the conversion coefficients depend strongly on the photon energy and angles of incidence for low-energy photons. In order to overcome the problem that the conversion coefficient of low energy rays changes greatly due to the small change of energy, a secondary standard ionization chamber was used to measure the personal dose equivalent directly. A matched reference field was established with 20-250 kV X-rays and correction factors with the Hp (10) chamber were calculated under these radiation qualities with different angles of incidence. The results showed that the differences were almost 22.7 % of correction factors for the low energy photons at angles of incidence 0°. With the conversion coefficient recommended in ISO 4037-3-2019, the performance of the chamber response with respect to Hp (10) in the energy range from 33 keV to 208 keV was within about 10 %, and in the energy range from 12 keV to 208 keV and for angles of incidence between 0° and 75° was within about ±19 %.